Crítica de la dominación, principio de anarquía y el redescubrimiento de lo político en Miguel Abensour (2016)
This text will follow the concept of domination as a paradigm of understanding of politics, domination, according to Abensour not disappear from the political sphere. Following the reflections of Hannah Arendt and Claude Lefort, who rediscovered in terms of freedom and action. Abensour make a joint proposal in which to recognize the overlapping of domination and the political proposal that is in the constant struggle against the domination that the full exercise of politics is achieved. This text seeks to rebuild conceptual paths drawing for Abensour regarding the articulation of paradigms of domination and political philosophy to propose an insurgent democracy in complement with the principle of anarchy leading to a proposal truly novel to conceive the political-democratic. A major conceptual transit for thinking about the possibility of an invigorating way the politics and democracy, a way to redirect the political to new paths of constant renewal, in the exercise of social in freedom.